The 100 Most Mentioned Glaucoma Articles Online With Highest Altmetric Attention Scores. Issue 1 (January 2022) - Chien, Jason L.; Sabharwal, Jasdeep; Namoglu, Esin C.; Ghassibi, Mark P.; Yuan, Melissa; Gandy, Christiana; Wei, Chapman; Somohano, Karina; Engelhard, Stephanie B.; Petrakos, Paul; Van Tassel, Sarah H.; Chien, Gwo-Farn; et al.
Abstract : Précis: Characteristics of the most mentioned glaucoma articles on the internet were analyzed, allowing a better understanding of the dissemination of glaucoma research to the general public. Purpose: The aim was to determine the 100 most mentioned articles on the internet in the field of glaucoma and analyze their characteristics. Materials and Methods: We identified the top 100 glaucoma articles with the highest Altmetric Attention Score (AAS), an automatically calculated metric for monitoring social media. Each article was evaluated for several characteristics including year of publication, title, journal name, journal impact factor (IF), article topic, article type, affiliation, and online mentions (news, blog, policy, Twitter, Facebook, etc.). Correlation analysis was conducted for AAS with these characteristics. Results: The selected 100 articles came from 44 journals with more than half (56%) published in ophthalmology-specific journals. There was no significant correlation between IF and number of articles in a specific journal or AAS ( P >0.1), but the number of articles in the top 100 was higher for ophthalmology journals with a higher IF ( P <0.05). Original study was the most common study type (87%), of which clinical observation study was the most common subgroup (40%). Epidemiology/risk factor and basic science were the most common article topics (each 24%), followed by medical treatment (13%). Article topics regarding medical treatment had a significantly greater AAS than other topics ( P <0.05). Of the top 5 articles, more than half (60%) were related to "Lifestyle choice" topics. Conclusions: There was no association between journal IF and AAS, consistent with previous studies. 90% of journals that had articles in the top 100 had a Twitter page. "Lifestyle choice" activities and other modifiable risk factors attracted significant online attention regarding glaucoma studies, with two of the top three most mentioned articles related to dietary intake. The present study thus provides a better understanding of online engagement with glaucoma research and the dissemination of this research to the general public. Abstract : Supplemental Digital Content is available in the text.